2009
DOI: 10.1111/j.1440-1584.2009.01056.x
|View full text |Cite
|
Sign up to set email alerts
|

The frontline and the ivory tower: A case study of service and professional‐driven curriculum

Abstract: The success of the program was due in large part to the relationship with professional bodies and close links with remote health services. We have described a number of lessons learnt from this experience that can be useful to other educational groups developing or revising their educational programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 5 publications
0
21
0
Order By: Relevance
“…In other Australian settings, unqualified staff would not provide this care. Over the past decade, there have been increased educational opportunities for RNs working in remote settings [49]. However, only 5% of the nurses who work in very remote Australian health services have specific skills and qualifications for their advanced practice role [29].…”
Section: Discussionmentioning
confidence: 99%
“…In other Australian settings, unqualified staff would not provide this care. Over the past decade, there have been increased educational opportunities for RNs working in remote settings [49]. However, only 5% of the nurses who work in very remote Australian health services have specific skills and qualifications for their advanced practice role [29].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have found community-based students do at least as well and may develop better clinical skills than students learning in more metropolitan, hospital-based training sites (Satran et al 1993;Worley et al 2000;Esterman et al 2004;Worley et al 2004;Iputo and Kwizera 2005;Power et al 2006;Lyon et al 2008;Wilson and Cleland 2008;Lenthall et al 2009;McLean et al 2010;Sen Gupta et al 2011). The experiential, community-engaged learning may also account for graduates of SHS-Palo being more likely to be practising in Public Health and in Family Medicine/General Practice.…”
Section: Discussionmentioning
confidence: 99%
“…Occasionally, they are made part of RCD teams, where they participate in decision-making on curriculum content (e.g. Lenthall, Wakerman, and Knight 2009;Paulsen and Peseau 1992). Fifth, within a responsive curriculum, courses are rarely taught by individual faculty members.…”
Section: Conceptualising Responsive Curriculum Developmentmentioning
confidence: 99%
“…In Ghana for example, universities offering professional programmes like accounting, education and natural resource management are researching the emerging needs of the profession (Ameyaw, Arts, and Wals 2016;Awayiga, Onumah, and Tsamenyi 2010) and are also reviewing or creating new curricula in response to the changing knowledge and skills requirements of employers (Kouwenhoven 2009). Some universities have introduced innovations aimed at enhancing interdisciplinarity in their curricula (Smith-Sebasto and Shebitz ARTICLE HISTORY received 6 august 2016 accepted 24 September 2017 KEYWORDS responsive curriculum; curriculum development practice; curriculum innovation; professional education; higher education; ghana 2013), using teaching and learning methods that are linked with problems in society and the world of work (Kiguli-Malwadde et al 2006;Lenthall, Wakerman, and Knight 2009) and that allow students to take greater responsibility for their own learning process (Cremers et al 2014). These innovations all aim to make these curricula more responsive to emerging societal needs.…”
Section: Introductionmentioning
confidence: 99%